2009
DOI: 10.1007/s00455-009-9251-y
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Complications Following Aluminium Phosphide Ingestion: An Emerging Issue Among Survivors of Poisoning

Abstract: Aluminium phosphide ingestion is the most common agricultural poisoning in suburban and rural India and with a high mortality rate. Among survivors of acute poisoning there are recent sporadic reports of esophageal complications such as esophageal strictures and tracheo-esophageal fistula. The present study was carried out to determine the incidence, natural history, and treatment outcome of local esophageal complications in survivors of aluminium phosphide poisoning with complaints of dysphagia. All confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…[374753] In follow-up among survivors, one-third of the patients had dysphagia due to esophageal complications, including esophageal stricture or tracheo-esophageal fistula. [54]…”
Section: Clinical Featuresmentioning
confidence: 99%
“…[374753] In follow-up among survivors, one-third of the patients had dysphagia due to esophageal complications, including esophageal stricture or tracheo-esophageal fistula. [54]…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Several patients have gone on to develop esophageal strictures (Nijhawan et al, 2006). A few cases have been reported with trachea-esophageal fistulae (Agrawal et al, 2010;Jain et al, 2010).…”
Section: Gastrointestinal Toxicitymentioning
confidence: 99%
“…In another report (39), dysphagia was observed in 38.87 % of survivors after a mean interval of 38.6 days from the day of AlP poisoning. Oesophageal strictures were seen in 32.2 % of the survivors.…”
Section: Gastrointestinal Toxicitymentioning
confidence: 99%
“…The neurological symptoms continued for 1.5 years post AlP exposure. Jain et al (39) reported dysphagia, oesophageal strictures, and tracheoesophageal fi stula in survivors a month after AlP exposure.…”
Section: Sequelae In Survivors?mentioning
confidence: 99%
See 1 more Smart Citation